The role of cracks and chlorides in corrosion of reinforced strain hardening cement-based composite (R/SHCC) - Paul, Suvash Chandra (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.